Signals from potential PVC indicators from refractory polymeric materials and natural fibers - Isabel Goßmann; Corinna Wirth; Barbara M. Scholz-Böttcher (PANGAEA, 2025)
This excel file contains information about several sources for refractory polymeric materials (e.g., soot) and natural fibers and their potential to generate PVC indicators when analyzed with Py-GC/MS.
In: Goßmann, I et al. (2025): Pyrolysis-GC/MS Reference Data for Polymeric and Refractory Materials to Evaluate C-PVC Indicator Specificity [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984614